Basilar trunk artery aneurysm presenting with brainstem stroke - Kavak, Rasime P. (Radiol Case Rep, 2020)
Basilar trunk artery aneurysms are extremely rare lesions that account for only 2.1% of all intracranial aneurysms. They are mostly recognized in patients around the age of 60, show a slight male predominance, and are associated with high morbidity and mortality. Chronic mural bleeding ectasia is the most common subtype of basilar trunk artery aneurysms. Its median maximum diameter ranges between 11 and 21 mm and is incidentally detected in more than half of the cases. Herein, we present a 58-year-old male patient who presented with brain stem stroke due to a chronic mural bleeding ectasia with a maximum diameter of 27 mm and died in the first week after admission.